Factor That Influences Stunting in Children Under 5 Years in Citrana Village, Oe-Cusse Municipality, Timor-Leste - Oqui, Maximiano; Abi, Norberto da Costa; Gomes , Lidia; Julieta Geri De Sena Amaral, Saturnina; Auxiliadora de Jesus Ximenes, Remigia; Evaristo Obeno, Olandino; Bartolomeu Freitas, Isabel (Rifa'Institute, 2025)
Introduction: Stunting is a chronic malnutrition problem caused by prolonged insufficient nutrient intake, indicated by height-for-age (HAZ) with a Z-score between –2 and –3 standard deviations. In 2020, UNICEF estimated that 149.2 million (22%) children under five worldwide were stunted. In Timor-Leste, the Ministry of Health reported a prevalence rate of 47.1%. Objective: This study aimed to identify factors influencing stunting among children under five in Citrana Village, Oe-Cusse Municipality, focusing on maternal education level, family income, maternal knowledge, exclusive breastfeeding, and complementary feeding. Methods: This analytical quantitative study employed a cross-sectional design with a purposive sample of 120 children under five. Data were collected through structured questionnaires and analyzed using SPSS with Chi-square and Spearman rank correlation tests. Results and Discussion: The results showed significant correlations between stunting and maternal education (p = 0.00; r = 0.705), family income (p = 0.00; r = 0.931), maternal knowledge (p = 0.00; r = 0.690), exclusive breastfeeding (p = 0.00; r = 0.543), and complementary feeding (p = 0.00; r = 0.602). Conclusions: To reduce stunting in Timor-Leste, targeted interventions are required to address direct causes, such as providing adequate nutrition and integrated management of childhood illness, and indirect causes, including improved sanitation, nutrition services, healthcare, parental education, and promotion of exclusive breastfeeding.